Disability, Diversity and Inclusive Education in Haiti Learning, Exclusion and Educational Relationships in the Context of Crises (Taylor & Francis, 2023)
Context, Crises, Disability, Diversity, Education, Educational, Exclusion, Haiti, Inclusive, Lainy, Rochambeau, Learning, Relationships
English
Keywords: Education; Educational psychology; Inclusive education / mainstreaming; Context, Crises, Disability, Diversity, Education, Educational, Exclusion, Haiti, Inclusive, Lainy, Rochambeau, Learning, Relationships